Use of tungsten material for the ITER divertor. (December 2016) - Hirai, T.; Panayotis, S.; Barabash, V.; Amzallag, C.; Escourbiac, F.; Durocher, A.; Merola, M.; Linke, J.; Loewenhoff, Th.; Pintsuk, G.; Wirtz, M.; Uytdenhouwen, I.
Abstract: Since the ITER divertor design includes tungsten monoblocks in the vertical target where heat loads are maximal, the design to protect leading edges as well as technology R&D for high performance armor-heat sink joint were necessary to be implemented. In the R&D, the availability of the technology was demonstrated by high heat flux test of tungsten monoblock components. Not systematically but frequently macro-cracks appeared at the middle of monoblocks after 20 MW/m 2 loading. The initiation of such macro-cracks was considered to be due to cyclic exposure to high temperature, ∼2000 °C, where creep, recrystallization and low cycle fatigue were concerned. To understand correlation between the macro-crack appearance and mechanical properties and possible update of acceptance criteria in the material specification, an activity to characterize the tungsten monoblocks was launched.